2015
DOI: 10.1039/c5sm01907a
|View full text |Cite
|
Sign up to set email alerts
|

Universal contact-line dynamics at the nanoscale

Abstract: The relaxation dynamics of the contact angle between a viscous liquid and a smooth substrate is studied at the nanoscale. Through atomic force microscopy measurements of polystyrene nanostripes we simultaneously monitor both the temporal evolution of the liquid-air interface and the position of the contact line. The initial configuration exhibits high curvature gradients and a non-equilibrium contact angle that drive liquid flow. Both these conditions are relaxed to achieve the final state, leading to three su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…In fact, when trying to fit the best line for the data of figure 5(d), we found an angle slightly different but with no significant improvement when comparing with the θ * correlation, so that we have kept this value for the sake of simplicity. The fact that this dewetting angle θ * appears to be almost independent on the substrates, the liquids and the film thicknesses, while our experiments and those of Rivetti et al (2015) concern film with totally different thickness is a very interesting and intriguing result. It might shed light on an universal dewetting mechanism that should deserve specific investigations in the future.…”
Section: The Stationary Contact Line (Scl) Regimementioning
confidence: 54%
See 3 more Smart Citations
“…In fact, when trying to fit the best line for the data of figure 5(d), we found an angle slightly different but with no significant improvement when comparing with the θ * correlation, so that we have kept this value for the sake of simplicity. The fact that this dewetting angle θ * appears to be almost independent on the substrates, the liquids and the film thicknesses, while our experiments and those of Rivetti et al (2015) concern film with totally different thickness is a very interesting and intriguing result. It might shed light on an universal dewetting mechanism that should deserve specific investigations in the future.…”
Section: The Stationary Contact Line (Scl) Regimementioning
confidence: 54%
“…The contact line relaxation starts at an angle given by the spreading dynamics (influenced by the drop impact velocity, the substrate wetting angle, and the drop size), and ends when θ reaches a critical value θ * enabling its depinning, required prelude to its receding motion. In the experiment of Rivetti et al (2015), this angle is θ * = 4.5 • ± 0.5 • and surprisingly appears to be independent of the liquid and of the film thickness.…”
Section: The Stationary Contact Line (Scl) Regimementioning
confidence: 79%
See 2 more Smart Citations
“…A recent study has demonstrated that a pronounced global bump exists in the dewetting of very flat droplets (h 0 /R(0) ≈ 0.02) even though the slip length is very small (b ≈ 10 −5 ) (Edwards et al 2016). In such cases, the transient global bump itself can be treated as quasistatic, as is the case in dewetting rims of thin liquid films (Redon et al 1991;Snoeijer & Eggers 2010;Rivetti et al 2015).…”
Section: Characteristic Of the Global Bumpmentioning
confidence: 99%